ANTIDIABETIC ACTIVITY OF EXTRACTS OF PITHECELLOBIUM DULCE BENTH LEAVES IN ALLOXAN INDUCED DIABETIC RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The objective of the present study was to study effect of Pithecellobium dulce Benth (P. dulce) leaves in alloxan induced diabetic rats. The P. dulce leaves were extracted by maceration and soxhelation method by using water and ethanol as solvent. Acute toxicity study was performed according to OECD 425 guidelines for both aqueous and ethanolic extracts of P. dulce leaves. The dose of 200 mg/kg and 400 mg/kg was selected for further studies. Animals were rendered diabetic by administration of alloxan (130 mg/kg, i.p.). The albino rats were divided in to seven groups with five animals in each group. Diabetic animals were treated with aqueous and ethanolic extract for 20 days. Then blood glucose, triglyceride, total cholesterol, urea, uric acid, creatinine, aspartate aminotransferase (AST), alanine transaminase (ALT) and glycogen level in liver, muscle and kidney were estimated according to standard procedures. The result shows significant decrease in blood glucose, triglyceride, total cholesterol, urea, uric acid, creatinine, AST and ALT level when compared to diabetic group. The liver and muscle glycogen level was increased significantly in extract treated groups when compared to diabetic control group. Both extract of P. dulce posses antidiabetic and hypolipidemic potential.